Application of Mycorrhiza Fertilizer on Productivity of Mungbean [Vigna radiata (L) Wilczeck] in Saline Soils - Mastika, Laily M.K.; Nuhagraningsih, Nuhagraningsih; B., Lukiati (Proceeding International Conference on Global Resource Conservation, 2015)
This research aims to determine the effect and the effective dose of Arbuscular Vesicular Mycorrhiza (AVM) biofertilizer on growth and production of mungbean or Vigna radiata (L) Wilczeck var. VIMA 1 in saline soils. This research used randomized block design consisting one factor with five replications. Arbuscular Vesicular Mycorrhiza (AVM) biofertilizer consisted of 5 levels, i.e 0 g/plant; 3 g/plant; 6 g/plant: 9 g/plant and 12 g/plant.Â Growth parameters included height, stem diameters, and leaf number, otherwise the production parameters included days to flowering, number of pods, pod weight, seed weight, wet and dry weight of shoots, wet and dry weight ofÂ roots and root diameters. Data obtained were analysed by single ANOVA and continued by LSD at the level 5%. The results showed that the dose 6 and 9 g/plant of AVM fertilizer was effective dose to improve plant growth and production of mungbean var. VIMA 1 in saline soils.Â Keywords: arbuscular vesicular mycorrhiza; saline soils; Vigna radiata var. VIMA 1